Training general practitioners in remote Western Australia in a method of screening and brief intervention for harmful alcohol use: A pilot study - Brennan, C.; Newton, M.; Wood, F.; Schug, S.; Allsop, Steve; Browne, A. (Blackwell Publishing, 2013)
Objective: High levels of alcohol-related harm are a salient feature of many rural communities in Australia. General practitioners (GPs) are uniquely placed to identify and treat patients with harmful alcohol use in remote settings, yet corresponding opportunities for education in effective brief psychological interventions for harmful alcohol use are limited. This study piloted a training model for alcohol screening and brief intervention for GPs working in Kalgoorlie-Boulder, a remote Western Australian community facing significant alcohol-related problems. Design: Observational pilot study. Setting: Primary care. Main outcome measure(s): Perceived role in responding to harmful alcohol use, and confidence and knowledge of alcohol screening and brief intervention; satisfaction with a short training session focused on alcohol screening and brief intervention; and impact of training on implementation of screening and brief intervention for harmful alcohol use. Results: Fifty per cent of GPs took up the training opportunity. GPs recognised their professional responsibility for conducting brief intervention but reported comparatively lower confidence and skills in implementing screening and intervention prior to training. The training improved knowledge and confidence in conducting alcohol screening and brief intervention. All GPs increased their frequency of alcohol screening, and 88% of GPs reported increasing the frequency of brief intervention at 6 months. Conclusions: Preliminary findings suggest that among participating GPs, subsequent compliance with identification and management of harmful alcohol use was improved. Further work examining methods to improve rural and remote GP participation in alcohol-related harm prevention training is required, as the potential impact on communities with disproportionately high alcohol-related difficulties is significant.